ANALISIS KELAYAKAN FINANSIAL INDUSTRI RUMAHTANGGA PANGAN (STUDI KASUS USAHA TAHU ALFARIA, KOTA KEFAMENANU) - Umbu Joka; Aprianus Tasik; Yosefina M.Fallo (Politeknik Negeri Lampung., 2020)
This study aims to determine the financial feasibility analysis of the Alfaria Food home industry. This research was conducted in August - September 2020 at the Home Industry of Tofu Alfaria Jln. El-Tari km 7 Kefamenanu. This research uses qualitative data methods and quantitative data. Qualitative data is in the form of non-financial aspects in the form of descriptive descriptions, tables, charts, and pictures while quantitative data is used to determine the state of the tofu industry financially such as Net Present Value (NPV), Internal Rate Of Return (IRR), Payback Period (PP), B. / C Ratio, Break Event Point (BEP) and Return Of Investment (ROI). The results of this study indicate that Alfaria Tofu Business is a kind of home industry. The results of the financial feasibility analysis show that the NPV value is Rp. 1.462.032.734.59, which means the NPV value> 1, therefore this company deserves to be continued, the IRR value is 53.8% which means the interest rate obtained from the tofu business is> compared to the KUR interest rate of 6.0% so that this company deserves to be continued and the B / C Ratio value is 8.8 which means that every 1 rupiah of costs incurred can provide a profit of 8.0 rupiah and the Payback Period is 11.41 which means that within 11 months 12 days of initial capital used to invest has been returned. Meanwhile, the analysis of Return of Investment (ROI) is 79.52, which means that the ability to measure the company's overall activities in the company, the higher this ratio, the better the company. Thus the Alfaria tofu business industry can be developed because it provides potential benefits.